Difference between revisions of "1962 AHSME Problems/Problem 3"

(Solution)
m (Solution)
Line 11: Line 11:
  
 
Therefore, our answer is <math>\boxed{\textbf{(B)}\ 0}</math>;
 
Therefore, our answer is <math>\boxed{\textbf{(B)}\ 0}</math>;
 +
 +
==See Also==
 +
[[Category:Introductory Algebra Problems]]
 +
{{MAA Notice}}

Revision as of 22:24, 10 November 2013

Problem

The first three terms of an arithmetic progression are $x - 1, x + 1, 2x + 3$, in the order shown. The value of $x$ is:

$\textbf{(A)}\ -2\qquad\textbf{(B)}\ 0\qquad\textbf{(C)}\ 2\qquad\textbf{(D)}\ 4\qquad\textbf{(E)}\ \text{undetermined}$

Solution

Let $y$ represent the common difference between the terms. We have $(x+1)-y=(x-1)\implies y=2$.

Substituting gives us $(2x+3)-2=(x+1)\implies 2x+1=x+1\implies x=0$.

Therefore, our answer is $\boxed{\textbf{(B)}\ 0}$;

See Also

The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

Invalid username
Login to AoPS